Effect of H2O on NO at oxy-fuel combustion condition of ethanol/NH3 and ethylene glycol/ NH3. Issue 1 (31st December 2023) - Yang, Yawei; Sun, Zhijun; Zhang, Anchao; Zhao, Chenxu; Wu, Qiyu; Li, Haixia
ABSTRACT: In this paper, the formation and reduction of NO during the oxidation of C2 H5 OH/NH3 and (CH2 OH)2 /NH3 under oxy-fuel conditions were experimentally investigated to understand the effect of high H2 O content on NO emission. We investigated the effects of high H2 O concentration, binding of H2 O to CO2, and OH/C ratio on NO formation and reduction. The results showed that the NO concentrations of C2 H5 OH/NH3 and (CH2 OH)2 /NH3 in different atmospheres increased with the increase in excess oxygen ratio (α) and showed the following order: O2 /N2 >O2 /Ar>O2 /CO2 and O2 /Ar/H2 O>O2 /CO2 /H2 O, with significant differences. When combusted under a dry atmosphere (without H2 O), (CH2 OH)2 /NH3 produces much less NO than C2 H5 OH/NH3 . Taking the O2 /N2 atmosphere as an example, the maximum NO conversion rate of (CH2 OH)2 /NH3 is 0.43, much lower than the maximum NO conversion rate of 0.60 for C2 H5 OH/NH3 . This is because (CH2 OH)2 has a larger OH/C ratio than C2 H5 OH, which will reduce the generation of CHi radicals and thus the chance that nitrogen will be oxidized to NO by CHi. The NO concentrations of both C2 H5 OH/NH3 and (CH2 OH)2 /NH3 will increase with H2 O under wet atmosphere oxygen-lean and oxygen-rich conditions. Of these, the 40% H2 O concentration condition has the most significant effect on NO emission. When the maximum NO emission was at α = 1.4in the O2 /Ar atmosphere with 40% H2 O, the NO emission of C2 H5 OH/NH3 was 437 PPM with a conversion rate of 0.63, and the NO emission of (CH2 OH)2 /NH3 was 449 PPM with a conversion rate of 0.42. This phenomenon may be due to the fact that decomposition of ethylene glycol consumes more OH radicals, thus leading to a much lower effect of H2 O on NO production during (CH2 OH)2 /NH3 combustion than during C2 H5 OH/NH3 .